EFFECT OF PERFORMANCE AND FEATURES ON CUSTOMER SATISFACTION IN CAFE ROPANG PLUS PLUS, PLUIT SAKTI, NORTH JAKARTA, INDONESIA - Karen, .; Rosanto, Stephanie (Journal of Business And Entrepreneurship, 2020)
This study aims to determine whether performance and features, as a part of product quality dimensions, influence consumer purchasing decisions at the Café Ropang Plus Plus, Pluit Sakti, North Jakarta. This research includes descriptive research using a quantitative approach. The sample in this study amounted to 105 respondents. Data collection techniques using questionnaires are tested for validity and reliability, and the data analysis technique used is multiple regression analysis. The sampling technique used is simple random sampling using the Slovin formula. Based on the analysis of statistical data, the indicators in this study are valid and reliable. In the normality test, the regression model in this study is normally distributed. Hypothesis using the t-test shows that the independent variable (performance and feature) affects the dependent variable (customer satisfaction) at the café. According to consumers, the independent variable is considered important when buying products from the café. The authors suggest that purchasing decisions will increase by conducting competitive pricing, while the location is already strategic and maintain the points valued well by customers.